Development of instruments for measuring critical attitudes of junior high school students - Ratna Dynawati; Ari Setiawan; Bounmy Phalychan (Universitas Sarjanawiyata Tamansiswa, 2022)
The goals of this study were: (1) to find out how teachers evaluate the critical attitudes of junior high school students toward information on social media; (2) to find out how a proper and standardized instrument for measuring the critical attitudes of junior high school students toward information on social media is made; and (3) to find out the criticality value of junior high school students after being measured using a valid and reliable instrument. This research is a type of research and development (R&D), and it uses the 10 steps of Djemari Mardapi's affective instrument development procedure. Based on the results of the study, the following conclusions can be made: (1) Teachers haven't been using proper and standard tools to measure students' critical attitudes so far. (2) The critical attitude instrument for junior high school students was made by putting together a hypothetical model with five indicators, having an expert validate it, giving it a readability test, and doing a lot of testing with 48 valid instruments (MSA > 0.5) with a reliability of 0.800 and a lot of testing with 38 valid instruments (MSA > 0.5) with a reliability of 0.813. (3) The results of measuring the critical attitudes of 32 students at Sentolo 4 Junior High School (SMP Negeri 4 Sentolo) obtained the following results: very high critical attitude values of 15.63%, high critical attitude values of 28.13%, low critical attitude values of 37.50%, and very low critical attitude values of 18.75%. The results of these tests show that most junior high school students are still not very critical.